2015
DOI: 10.5713/ajas.14.0825
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Temperature and Humidity on Pregnancy Rate of Murrah Buffaloes under Subtropical Climate

Abstract: Heat stress has adverse effects on fertility of dairy animals. Decline in fertility is linearly associated with an increase in combination of both temperature and humidity. The purpose of this study was to investigate the relationship between temperature humidity index (THI) and the pregnancy rate of Murrah buffaloes in a subtropical climate. The effects of genetic and non-genetic factors viz., sire, parity, period of calving and age group at first calving were found non-significant on pregnancy rate. The effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
32
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(35 citation statements)
references
References 21 publications
(25 reference statements)
3
32
0
Order By: Relevance
“…All these THI models were used in a study conducted by Dash et al . [ 24 ] at Karnal in India. Month wise average THI values with seven different THI models during 20 years from 1993 to 2012 were presented in Figure-1 .…”
Section: Different Heat Stress Models For Formulating Thi and Hlimentioning
confidence: 99%
See 2 more Smart Citations
“…All these THI models were used in a study conducted by Dash et al . [ 24 ] at Karnal in India. Month wise average THI values with seven different THI models during 20 years from 1993 to 2012 were presented in Figure-1 .…”
Section: Different Heat Stress Models For Formulating Thi and Hlimentioning
confidence: 99%
“…All these environmental factors are pooled to produce heat stress on animals, which is defined as any combination of environmental variables producing conditions that are higher than the temperature range of the animal’s thermoneutral zone (TNZ) [ 5 ]. Heat stress has an adverse effect on reproduction traits of dairy cattle [ 6 , 7 ] and buffaloes [ 8 ]. The negative influence of heat stress on reproduction traits of cattle and buffaloes can be quantified through formulating temperature humidity index (THI).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…THI exceeding 72 decreases the growth, milk yield and reproductive performance of buffaloes. Dash et al (2015) reported that the threshold THI for pregnancy rate was identified as 75 in Murrah buffaloes (Dash et al, 2015). Although we cannot determine the threshold THI for pregnancy rate in Dehong dairy buffaloes, the average high THI in summer appeared to restrict their day 90 pregnancy/AI, especially for heifer buffaloes.…”
Section: Advances In Animal and Veterinary Sciencesmentioning
confidence: 78%
“…Climate change has a great impact on the reproductive activity of cattle and buffaloes (Dash et al, 2015). …”
Section: Effect Of Heat Stress On Animal Reproductionmentioning
confidence: 99%